Equilibrium in the Pricing of Capital Assets, Risk-Bearing Debt Instruments, and the Question of Optimal Capital Structure: A Comment - Imai, Yutaka; Rubinstein, Mark (Journal of Financial and Quantitative Analysis, 1972)
Yutaka Imai, Mark Rubinstein, Equilibrium in the Pricing of Capital Assets, Risk-Bearing Debt Instruments, and the Question of Optimal Capital Structure: A Comment, The Journal of Financial and Quantitative Analysis, Vol. 7, No. 4 (Sep., 1972), pp. 2001-2003